Total Synthesis of (–)-Invictolide - Yadav, Jhillu S.; Lakshmi, K. Anantha; Reddy, N. Mallikarjuna; Prasad, Attaluri R.; Al Khazim Al Ghamdi, Ahmad (Synthesis, 2012)
A convergent approach to the total synthesis of (–)-invictolide, a component of the queen recognition pheromone of Solenopsis invicta, is described. Key steps involve the desymmetrization of a bicyclic olefin with Brown’s chiral hydroboration, C–C bond formation, 1,3-syn reduction, and oxidative lactonization of a 1,3,5-triol with TEMPO/PhI(OAc)2.
Keywords: pheromones; desymmetrization strategy; syn-1,3-reduction; oxidative lactonization